Application of 3D Printing to the Manufacturing of Groundwater Velocity Probes. Issue 2 (8th March 2017) - Walter, K.; Devlin, J.F.
Abstract: For the purposes of risk mitigation and remediation design, Darcy's Law calculations, that are typically used to estimate flow direction and magnitude, can be usefully supplemented with more direct measurements. The point velocity probe (PVP), which measures groundwater velocity by conducting a mini‐tracer test across a cylindrical probe surface, was developed to address this need. Laboratory and field experiments have shown that these probes can provide accurate velocity magnitude and direction measurements at the centimeter scale. In an effort to streamline the production of PVPs, three‐dimensional (3D) printing was investigated. The 3D printer produces a plastic probe body with designated detector and injection port locations. The subsequent installation of injection lines and detector wires requires, for a single‐port probe, no longer than 1–2 h of assembly time, compared to approximately 10 h to assemble previous designs (mainly determined by injection port installation). Probes can be printed in batches with the number of units made depending on the printer and probe size. Laboratory tests of the original PVP models yielded velocity magnitudes and directions with average errors (from expected values) of ±9% to ±15% and ±8°, respectively. A printed PVP was tested in a nested storage tank system (NeST) packed with sand that mimics flow conditions through a sandy aquifer. The probe was tested at multiple pumping rates with the injector port at angles of ( α =) 30°, 45°, and 75° from the expected linear flow direction. The printed PVPs provided an average magnitude percent error of ±13.5% and an average direction error of ±4°. This shows that in laboratory tests, printed PVPs performed as well as the original probes previously reported, making them viable units for field applications as well as being quicker to assemble than the earlier designs. Abstract : Article impact statement : 3D printing permits rapid, high quality, point velocity probe (PVP) fabrication in less time than was previously possible, making the technology increasingly accessible.